Effect of Yttrium Oxide Impurities on the Structure and Properties of Metallic Hafnium - Chornobuk, S.V.; Cherednik, M.I.; Makara, V.A. (Physics and Chemistry of Solid State, 2016)
The influence of yttrium oxide impurity content of 0 to 0.4 wt.% on the structure and microhardness metal hafniuminvestigated. It is shown that grain size decreases and the Microhardness of hafnium increases monotonically with increasing content of impurities, while increasing Y2O3 content more than 0.3 wt.% is cracking material.